Does Delaying Surgical Resection After Neoadjuvant Chemoradiation Impact Clinical Outcomes in Locally Advanced Rectal Adenocarcinoma?: A Single-Institution Experience. (February 2018) - Nguyen, Phuong; Wuthrick, Evan; Chablani, Priyanka; Robinson, Andrew; Simmons, Luke; Wu, Christina; Arnold, Mark; Harzman, Alan E.; Husain, Syed; Schmidt, Carl; Abdel-Misih, Sherif; Bekaii-Saab, Tanios; et al.
Abstract : Objectives: Surgical resection for locally advanced rectal adenocarcinoma commonly occurs 6 to 10 weeks after completion of neoadjuvant chemoradiation (nCRT). We sought to determine the optimal timing of surgery related to the pathologic complete response rate and survival endpoints. Methods: The study is a retrospective analysis of 92 patients treated with nCRT followed by surgery from 2004 to 2011 at our institution. Univariate and multivariate analyses were performed to assess the impact of timing of surgery on locoregional control, distant failure (DF), disease-free survival, and overall survival (OS). Results: Time-to-surgery was ⩽8 weeks (group A) in 72% (median 6.1 wk) and >8 weeks (group B) in 28% (median 8.9 wk) of patients. No significant differences in patient characteristics, locoregional control, or pathologic complete response rates were noted between the groups. Univariate analysis revealed that group B had significantly shorter time to DF (group B, median 33 mo; group A, median not reached, P =0.047) and shorter OS compared with group A (group B, median 52 mo; group A, median not reached, P =0.03). Multivariate analysis revealed that increased time-to-surgery showed a significant increase in DF (HR=2.96, P =0.02) and trends toward worse OS (HR=2.81, P =0.108) and disease-free survival (HR=2.08, P =0.098). Conclusions: We found that delaying surgical resection longer than 8 weeks after nCRT was associated with an increased risk of DF. This study, in combination with a recent larger study, questions the recent trend in promoting surgical delay beyond the traditional 6 to 10 weeks. Larger, prospective databases or randomized studies may better clarify surgical timing following nCRT in rectal adenocarcinoma.